ANALISIS DAN PERANCANGAN JARINGAN VIRTUAL PADA SMK NEGERI 2 KOTA JAMBI - Joni, Joni; Assegaf, Setiawan (Jurnal Manajemen Sistem Informasi, 2019)
Computer networks today become the need to build a very wide communication because it can reachseveral areas with different geographical location. Institution engaged in education makes computernetwork as a subject on IT department. The computer network is the set of interconnections between twoor more autonomous computers connected to the cable or wireless transmission medium.The applicationof computer network needs many equipments and materials. To be more efficient in its use it can be builtvirtual network using full virtualization technique, and in making virtual machine used VirtualBox astool. This research makes five virtual machines in one host computer called host, where linux debian asserver, mikrotik OS as router and windows xp, windows 7 and windows 10 as client called guest. Fifthvirtual machine uses a different IP address but still connected to each other on a local network or internet.This virtual network can be used as a solution to the problem of the lack of hardware availability (PC),facilitate teachers and learners in understanding the process of network communication (ping process andaccess) and can support the implementation of computer network learning process, especially in SMKNegeri 2 Kota Jambi.